PACIFIC ISLANDS FORUM DIPLOMACY FOR CLIMATE JUSTICE AT COP29 - Ika Sri Hastuti; rekha kersana (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
Climate change represents an existential and multidimensional challenge for Pacific Island countries, despite their limited contribution to global greenhouse gas emissions. This article examines how the Pacific Islands Forum (PIF) transformed regional climate vulnerability into collective diplomatic agency at COP29 in Baku. Using qualitative document analysis, the study examines UNFCCC decisions, PIF and SPREP documents, regional declarations, official statements, and relevant academic literature. Climate diplomacy serves as the primary analytical framework, supported by international regime theory and regional organisation perspectives. The findings demonstrate that PIF employed four mutually reinforcing strategies: coalition building, normative pressure, agenda-setting, and evidence-based negotiation. These strategies strengthened Pacific visibility and helped sustain climate finance, the 1.5°C objective, adaptation, and loss and damage on the negotiation agenda. However, PIF's influence remained constrained by material power asymmetries and the distributive limitations of COP29's climate-finance outcome. The study concludes that PIF diplomacy was procedurally effective and normatively influential, but substantively constrained. Keywords: climate diplomacy; climate justice; COP29; Pacific Islands Forum; small island states